The Effect Of Working Capital Efficiency And Liquidity On Profitability: Case Study at Food and Beverage Industry Listed in Indonesian Stock Exchange Period 2015-2020 - Wadudi Wibowo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine the effect of working capital efficiency and liquidity on profitability. The variables used in this research are working capital efficiency and liquidity of independent variable and profitability as dependent variable. Working capital efficiency is measured by working capital (X1), liquidity is measured by the current ratio (X2), and profitability measured by return on assets (Y). The object of this research is conducted in the food and beverage industry in Indonesia Stock Exchange period 2015-2020, as many as 8 companies. The samples used are 48 companies. The regression model using panel data regression and regression model used is the Common Effect Model. In statistical test study states that the working capital turnover (X1) is not significant to the return on assets (Y) and the current ratio (X2) has a significant positive effect partially on return on asset (Y). Keywords: Working Capital Turnover, Current Ratio, Return on Asset